Nursing Care Documentation Analysis Based on Standard Nursing Care Evaluation Instruments - Usman Sasyari; Fitri Nurlina; Yuyun Solihatin (HealthCare Nursing Journal, 2023)
The completeness of nursing care documentation has been set at a minimum standard of 85%. This is to show the patient's condition which is seen not only from the level of pain but also from the type, quality and quantity of services that have been provided by nurses in meeting patient needs. This study aims to analyze the completeness of nursing care documentation based on SAK evaluation instruments. The method used is descriptive with a documentary study using SAK. The results showed that the completeness of the assessment was 100%, the diagnosis was 90%, the intervention was 86.6%, the implementation was 100%, and the progress record was 100%. It is recommended that there be continuous and consistent evaluation by the field of nursing on nursing care documentation.